Assessment of control tools for utilizing excess distributed photovoltaic generation in domestic electric water heating systems. (15th October 2021) - Yildiz, Baran; Roberts, Mike; Bilbao, Jose I.; Heslop, Simon; Bruce, Anna; Dore, Jonathon; MacGill, Iain; Egan, Renate J.; Sproul, Alistair B.
Highlights: An intelligent water heating control (IWHC) was developed to utilize PV generation. Two other control tools, diverter and timer were studied and tested for comparison. Energy simulation models were developed and extended to 380 Australian households. Household hot water profile and tariffs impacted operational and financial performance. Diverter had best operational performance and IWHC had best financial performance. Abstract: Appliance level control and automation is an increasingly promising demand-side management tool with growing installation of advanced metering, monitoring and control infrastructure in both residential and commercial contexts. Successful implementation of appliance control and automation can alleviate network peak demand and improve distributed photovoltaic (D-PV) self-consumption to reduce its network voltage and reverse power flow impacts. Domestic electric water heating (DEWH) systems are widely deployed globally and have one of the highest peak power draw and overall energy consumption of household appliances. DEWH storage tanks offer large thermal energy storage capacity which can be used for shifting demand to lower demand periods. With growing D-PV deployment, they also offer the opportunity to store excess generation that would be otherwise exported to the grid. In this work, an intelligent water heating control tool (IWHC) is developed to store excess D-PV generation in DEWH storage tanks as thermal energy, according to the D-PV generation characteristics, household electricity consumption, hot water draw (HWD) patterns, and real time energy monitoring. The IWHC tool was installed and tested in nine Australian households with D-PV and DEWH systems. For performance comparison, two other commercially available control tools, timer, and diverter, were installed and tested in eleven other households with D-PV and DEWH systems. For each control tool, energy simulation models were developed, and the collected field performance data was used to validate the models. The validated simulation models were extended to a broader set of 380 Australian households with a year of D-PV, household and DEWH electricity consumption data. The results indicate that, on average, households can utilize 2.4 kWh, 1.8 kWh and 3.4 kWh of daily excess D-PV generation for water heating, using the IWHC, timer and diverter, respectively. Financial savings from the control of DEWH are highly dependent on households' tariffs and daily HWD profiles. Under the most optimal morning dominant HWD profile scenario and with an average tariff, households can, on average, save $100, $80, and $170 per year with the IWHC, timer and diverter, respectively. However, the diverter's superior field performance comes with higher capital cost, making IWHC the most attractive option.